1999
DOI: 10.1097/00005392-199902000-00099
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION AND POSSIBLE FUNCTIONAL ROLE OF THE beta 3-ADRENOCEPTOR IN HUMAN AND RAT DETRUSOR MUSCLE

Abstract: These results suggest that beta3-AR agonists may be effective in the treatment of urinary frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 16 publications
0
77
0
Order By: Relevance
“…The β3-AR 8 is the predominant -AR in the human bladder [9][10][11] , and has recently become a therapeutic target for bladder storage symptoms. 12,13 However, the site(s) of action and mechanisms involved have not been…”
Section: Discussionmentioning
confidence: 99%
“…The β3-AR 8 is the predominant -AR in the human bladder [9][10][11] , and has recently become a therapeutic target for bladder storage symptoms. 12,13 However, the site(s) of action and mechanisms involved have not been…”
Section: Discussionmentioning
confidence: 99%
“…However, β3-ARs account for more than 95% of all β-AR mRNA in the human bladder and are thought to be the main β-ARs mediating human detrusor relaxation [Takeda et al 1999[Takeda et al , 2000Igawa et al 2010]. β3-ARs have been found to be highly and preferentially expressed on urinary bladder tissues, including the urothelium, interstitial cells, and detrusor smooth muscle [Andersson et al 2009;Andersson and Arner, 2004;Otsuka et al 2008;Limberg et al 2010;Fujimura et al 1999].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…It has been shown that b 3 -AR agonists increase bladder capacity with no change in micturition pressure and residual volume. 108,[121][122][123][124] For example, Hicks et al 124 studied the effects of the selective b 3 -AR agonist GW427353 in the anesthetized dog and found that the drug evoked an increase in bladder capacity under conditions of acid-evoked bladder hyperactivity without affecting voiding. b 3 -AR selective agonists are currently being evaluated as potential treatment for OAB in humans.…”
Section: 105mentioning
confidence: 99%